THE LEGAL NATURE OF THE “ATTORNEY’S INVESTIGATION” AS OF A LEGAL INSTITUTION (Law and world, 2017)
This paper aims to provide readers with the new legal institution, which is called the ‘attorney’s investigation’. In 2009, adopted criminal procedure code introduced innovation in criminal proceedings. At a ﬁ rst glance, the human rights are more effectively dealt, afﬁ rmative action mechanisms are increased in favor of accused and defendant. The new law granted to defendant the right to conduct an independent investigation in the criminal case and to introduce to the court the evidence obtained as a result of the investigation that has equal power in comparison with the one obtained by the prosecution. The paper will focus on conceptual issues of“attorney’s investigation“ and examine its legal nature, goals and objectives. The paper will also discuss different ways and possibilities for the lawyers to obtain the evidence during the“attorney’s investigation“ process.